Lyons: Shift diaster fund control - Wildermuth, Todd (Raton, NM Raton Range, 1996)
This article is about the money Cimarron received from the Tornado disaster clean up fund.
Newspaper article + Photographs of Tornado damage and Colfax Count road department crew
Mater List Item # 77
File location is in the New Mexico File Cabinets
Keywords: Lyons, Pat -- New Mexico State Senator; Johnson, Gary -- New Mexico Governor; Federal Emergency Management Agency - FEMA; Village of Cimarron; Red Cross; International Bank; Disaster Funds; State Aid; Federal Aid; Financial Aid; Tornado Damage; Tornado Disasters; Cimarron, New Mexico